Stereoselective synthesis of oxazolidinonyl-fused piperidines of interest as selective muscarinic (M1) receptor agonists: a novel M1 allosteric modulator. Issue 6 (15th January 2016) - Broadley, Kenneth J.; Buffat, Maxime G. P.; Burnell, Erica; Davies, Robin H.; Moreau, Xavier; Snee, Stephen; Thomas, Eric J.
Abstract : Syntheses of (1 RS, 2 SR, 6 SR )-2-alkoxymethyl-, 2-hetaryl-, and 2-(hetarylmethyl)-7-arylmethyl-4, 7-diaza-9-oxabicyclo[4.3.0]nonan-8-ones, of interest as potential muscarinic M1 receptor agonists, are described. Abstract : Syntheses of (1 RS, 2 SR, 6 SR )-2-alkoxymethyl-, 2-hetaryl-, and 2-(hetarylmethyl)-7-arylmethyl-4, 7-diaza-9-oxabicyclo[4.3.0]nonan-8-ones, of interest as potential muscarinic M1 receptor agonists, are described. A key step in the synthesis of (1 RS, 2 SR, 6 SR )-7-benzyl-6-cyclobutyl-2-methoxymethyl-4, 7-diaza-9-oxabicyclo[4.3.0]nonan-8-one, was the addition of isopropenylmagnesium bromide to 2-benzyloxycarbonylamino-3- tert -butyldimethylsilyloxy-2-cyclobutylpropanal. This gave the 4- tert -butyldimethylsilyloxymethyl-4-cyclobutyl-5-isopropenyloxazolidinone with the 5-isopropenyl and 4- tert -butyldimethylsilyloxymethyl groups cis -disposed about the five-membered ring by chelation controlled addition and in situ cyclisation. This reaction was useful for a range of organometallic reagents. The hydroboration–oxidation of (4 SR, 5 RS )-3-benzyl-4-( tert -butyldimethylsilyloxymethyl)-4-cyclobutyl-5-(1-methoxyprop-2-en-2-yl)-1, 3-oxazolidin-2-one gave (4 SR, 5 RS )-3-benzyl-4-( tert -butyldimethylsilyloxymethyl)-4-cyclobutyl-5-[( SR )-1-hydroxy-3-methoxyprop-2-yl]-1, 3-oxazolidin-2-one stereoselectively. 4, 7-Diaza-9-oxabicyclo[4.3.0]nonan-8-ones with substituents at C2 that could facilitate C2 deprotonation were unstable with respect to oxazolidinone ring-opening and this restricted both the synthetic approach and choice of 2-heteroaryl substituent. The bicyclic system with a 2-furyl substituent at C2 was therefore identified as an important target. The addition of 1-lithio-1-(2-furyl)ethene to 2-benzyloxycarbonylamino-3- tert -butyldimethylsilyloxy-2-cyclobutylpropanal gave (4 SR, 5 RS )-4- tert -butyldimethylsilyloxymethyl-4-cyclobutyl-5-[1-(2-furyl)ethenyl]-1, 3-oxazolidinone after chelation controlled addition and in situ cyclisation. Following oxazolidinone N -benzylation, hydroboration at 35 °C, since hydroboration at 0 °C was unexpectedly selective for the undesired isomer, followed by oxidation gave a mixture of side-chain epimeric alcohols that were separated after SEM-protection and selective desilylation. Conversion of the neopentylic alcohols into the corresponding primary amines by reductive amination, was followed by N -nosylation, removal of the SEM-groups and cyclisation using a Mitsunobu reaction. Denosylation then gave the 2-furyloxazolidinonyl-fused piperidines, the (1 RS, 2 SR, 6 SR )-epimer showing an allosteric agonistic effect on M1 receptors. Further studies resulted in the synthesis of other 2-substituted 4, 7-diaza-9-oxabicyclo[4.3.0]nonan-8-ones and an analogous tetrahydropyran.